2009
DOI: 10.1093/eurjhf/hfp109
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width predicts long‐term outcome regardless of anaemia status in acute heart failure patients

Abstract: AimsTo study the long-term prognostic value of red blood cell distribution width (RDW) in patients hospitalized with acute heart failure (AHF) and to compare the value of this measurement with haemoglobin levels and anaemia status. Methods and resultsDuring a 2-year period, we studied 628 consecutive patients (aged 71 years [interquartile range, IQR: 61 -77], 68% male) hospitalized with AHF. Demographic, clinical, echocardiographic, and laboratory characteristics were registered at discharge and patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
145
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(175 citation statements)
references
References 32 publications
18
145
3
3
Order By: Relevance
“…15,20,21) However, it has already been concluded that RDW predicts poor long-term outcome regardless of anemia status in AHF patients. 14,22,23) We observed that RDW was associated with low hemoglobin and depressed MCV, which are consistent with a state of impaired iron mobilization. RDW was an independent predictive factor after adjustment for hemoglobin in short-term outcome, though it had limitations in predicting 30-day clinical outcome.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…15,20,21) However, it has already been concluded that RDW predicts poor long-term outcome regardless of anemia status in AHF patients. 14,22,23) We observed that RDW was associated with low hemoglobin and depressed MCV, which are consistent with a state of impaired iron mobilization. RDW was an independent predictive factor after adjustment for hemoglobin in short-term outcome, though it had limitations in predicting 30-day clinical outcome.…”
Section: Discussionsupporting
confidence: 77%
“…Ample evidence has demonstrated the value of RDW for predicting long-term adverse outcome in patients with AHF 5,14) and CHF.…”
Section: Discussionmentioning
confidence: 99%
“…At the present time, it is well know that atherosclerosis is chronic inflammatory disease and varied causative cytokines such as TNF-α, IL-1b, and IL-6 are released in its process (11,12). These increased inflammatory cytokines in blood stream may have a suppressing effect on erythropoietin (Epo) and hemoglobin synthesis that this situation causes chronic inflammatory anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Originally it is used to distinguish types of anemia. However, it has been recently demonstrated that an increase in the RDW values may be associated with heart failure, coronary ar tery disease or peripheral artery disease [1][2][3][4]. Moreover, RDW is believed to be an indicator of inflammation as well, since an increase in this value might be a result of oxidative stress on the erythrocytes.…”
Section: Introductionmentioning
confidence: 99%